Cobalt‐Catalyzed Hydrosilation/Hydrogen‐Transfer Cascade Reaction: A New Route to Silyl Enol Ethers. Issue 31 (18th June 2013) - Lyons, Thomas W.; Brookhart, Maurice
<x xml:space="preserve">Abstract</x> Capitalizing on cobalt: A new route to silyl enol ethers employing a Co‐catalyzed cascade reaction featuring a tandem hydrosilation/hydrogen‐transfer reaction is reported. The low catalyst loading, mild reaction conditions, and unique η2‐silane resting state showcase the impressive utility of this seldom used transition‐metal catalyst in CH activation reactions (see scheme; VTMS = vinyltrimethylsilane; Cp* = 1, 2, 3, 4, 5‐pentamethylcyclopentadiene).<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>